Permainan Bola Berwarna untuk Meningkatkan Kemampuan Mengenal Warna pada Anak Usia 4-5 Tahun di PAUD IT Al Ghazali Modern School Palangka Raya - Devi Oktavia; Sri Hidayati; Aghnaita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to improve the ability to recognize colors in children aged 4-5 years through the implementation of colored ball games. The background of this study is based on the low ability of children to recognize colors as seen in the pre-cycle results, namely an average achievement of only 33% with the category of Starting to Develop (MB). This study uses classroom action research (CAR) which is carried out in two cycles with the Kemmis and MC Taggart models; each cycle consists of two meetings. The research location was carried out at PAUD IT Al Ghazali Modern School Palangka Raya. The research subjects consisted of 17 children aged 4-5 years class A1 Abdullah bin Azzar. Data collection techniques used observation, documentation and interviews which were analyzed descriptively with a percentage. Based on the results of the study, it showed that there was a significant increase in the development of children's ability to recognize colors. In cycle I, the average achievement of children's ability to recognize colors was 64% (Developing According to Expectations), but had not met the success criteria of 76% (Developing Very Well) so that it was continued in cycle II resulting in an average of 89.5% which met the success criteria of Developing Very Well (BSB). These findings indicate that the application of colored ball games is effective in improving the color recognition abilities of children aged 4-5 years.